황산바나듐 모의용액으로부터 Alamine336에 의한 바나듐 용매추출의 최적조건 연구 - 안종관; Jong Gwan Ahn; 안재우; Jae Woo Ahn (대한금속·재료학회지, 46(12), 2008)
The solvent extraction process for the recovery of vanadium from leaching solution of SCR(selective catalytic reduction) spent catalyst was investigated by using Alamine336 as an extractant. The effects of experimental conditions, such as initial pH and concentration of sulfate ion, and ammonia concentration of stripping solution were studied. The extraction percentage of vanadium were increased with the increase of initial pH of leaching solution and decreased with the increase of sulfate ion. More than 99% of vanadium in leaching solution were extracted and stripped at the A/O ratio of 1.0 in 2 stages. On the basis of these results, an optimum solvent extraction process which vanadium was effectively recovered from SCR spent catalyst was proposed.